2004
DOI: 10.1176/appi.ajp.161.7.1181
|View full text |Cite
|
Sign up to set email alerts
|

A Voxel-Based PET Investigation of the Long-Term Effects of “Ecstasy” Consumption on Brain Serotonin Transporters

Abstract: These findings support the hypothesis of MDMA-induced protracted alterations of the serotonergic system and indicate that the reduced availability of serotonin transporter, as measured by PET, might be reversible. Women appear to be more susceptible than men to MDMA-induced alterations of the serotonergic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
127
2
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 24 publications
16
127
2
7
Order By: Relevance
“…Consistent with the outcomes of previous studies (e.g., Buchert et al 2004;Thomasius et al 2006) the results revealed that SERT densities were significantly reduced in all cortical areas with the occipital and temporal cortices most affected. No significant differences in SERT binding emerged in the basal ganglia structures or the thalamus.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the outcomes of previous studies (e.g., Buchert et al 2004;Thomasius et al 2006) the results revealed that SERT densities were significantly reduced in all cortical areas with the occipital and temporal cortices most affected. No significant differences in SERT binding emerged in the basal ganglia structures or the thalamus.…”
Section: Discussionsupporting
confidence: 92%
“…The purpose of the present study was to produce robust depletions in order to evaluate the long-term behavioral consequences for those heavy users who do experience serotonin depletion rather than model typical human use patterns. An emerging literature in humans and animals does suggest that humans who are heavy MDMA users experience measurable loss of serotonergic markers (Buchert et al 2004;De Win et al 2004;Ricaurte et al 2000;Semple et al 1999), although recovery in these markers may occur (Buchert et al 2004;De Win et al 2004) and the mediating mechanisms are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies report greater loss of serotonin terminal markers in women than in men (Buchert et al 2004;De Win et al 2004;McCann et al 1994). These differences in humans could reflect the average greater dose women ingest due to the fixed dose that most human users receive rather than a specific vulnerability to serotonin depletion in women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations